Echinococcal Cyst Blockade — the Rare Cause of Acute Pancreatitis and Obstructive Jaundice - S. A. Budzinskiy; S. G. Shapovaliants; R. V. Plakhov; M. V. Murashkina; E. A. Vorobyeva; D. R. Berdieva; P. V. Usyaky; E. D. Fedorov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: demonstrate an algorithm for the diagnosis and treatment of acute pancreatitis and obstructive jaundice caused by obstruction of the terminal part of the common bile duct by daughter echinococcal cyst.Key points. The article presents a clinical case of acute echinococcal obstruction of the terminal part of the common bile duct in a patient with a complicated course of liver echinococcosis. A 33-year-old man was hospitalized with epigastrium and right hypochondrium pains and jaundice. In 2019 the patient underwent the removal of a cyst in the 7th liver segment and cholecystectomy for liver and gallbladder echinococcal lesions. Laboratory research revealed leukocytosis, hyperbilirubinemia and an increase in the transaminases level. Transabdominal ultrasound showed signs of dilatation throughout bile ducts. Duodenoscopy revealed a fixed yellowish-white oval formation with transluent capsule, completely blocking bile and pancreatic juice outflow at the major duodenal papilla. After non-annulation endoscopic papillotomy, migration of the substrate (echinococcal cyst) into the duodenum was noted, active flow of bile and pancreatic secretions was restored. Oral transpapillary cholangioscopy was performed for a detailed bile ducts examination. It revealed no echinococcal cysts, residual parasitic structures or biliary tree lesions. The treatment was completed with pancreatic stenting. After complex treatment in the intensive care and surgery unit with complete condition stabilization, the patient was discharged with recommendations for further treatment in a specialized clinic.Conclusion. Migration of a daughter cyst from the echinococcal liver focus can cause acute blockade of the terminal part of the common bile duct and acute obstructive pancreatitis. The combination of clinical, radiological and endoscopic methods allows to diagnose and eliminate this rare complication of liver echinococcosis with subsequent successful treatment.